2013
DOI: 10.1523/jneurosci.1099-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Otx2 in the Adult Retina Disrupts Retinal Pigment Epithelium Function, Causing Photoreceptor Degeneration

Abstract: Photoreceptors are specialized neurons of the retina that receive nursing from the adjacent retinal pigment epithelium (RPE). Frequent in the elderly, photoreceptor loss can originate from primary dysfunction of either cell type. Despite intense interest in the etiology of these diseases, early molecular actors of late-onset photoreceptor degeneration remain elusive, mostly because of the lack of dedicated models. Conditional Otx2 ablation in the adult mouse retina elicits photoreceptor degeneration, providing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
83
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(85 citation statements)
references
References 57 publications
2
83
0
Order By: Relevance
“…From the literature, we added additional possible connections into the network. The direct relations reported in the RPE are regulation of Mitf and Otx2 by ␤-catenin (14) and regulation of Rdh5 by OTX2 (16). The direct relations reported in non-RPE cells are regulation of MITF by SOX9 in human skin melanocytes (67) and regulation of Sox9 by LHX2 in mouse skin keratinocytes (26) (Fig.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…From the literature, we added additional possible connections into the network. The direct relations reported in the RPE are regulation of Mitf and Otx2 by ␤-catenin (14) and regulation of Rdh5 by OTX2 (16). The direct relations reported in non-RPE cells are regulation of MITF by SOX9 in human skin melanocytes (67) and regulation of Sox9 by LHX2 in mouse skin keratinocytes (26) (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…The critical role of OTX2 in RPE development is well documented (12,15). Its importance in maintaining adult RPE functions has also been reported recently (16). In our previous studies, we identified sex-determining region Y box 9 (SOX9) as a key regulator that activates the human BEST1 promoter in the RPE through interaction with MITF and OTX2 (17).…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…OTX2, a paired-type homeodomain protein, is important for specification and postmitotic function of PRs [73], bipolar neurons, and RPE [74][75][76][77]. OTX2 [+] cells first appear in the developing PRs, and then in the bipolar and RPE cells during mammalian retinogenesis [78].…”
Section: Finding Layers Of Early Retinal Cell Types Synaptogenesis mentioning
confidence: 99%